2013
DOI: 10.1016/j.otsr.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of radiographic signs of slipped capital femoral epiphysiolysis sequelae in hip arthroplasty candidates for coxarthrosis

Abstract: Level III. Diagnostic prospective study with a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
18
1
1
Order By: Relevance
“…There are several studies available describing the prevalence of a slip-like morphology for different study populations. A prevalence of 13% was found for healthy young adults [9]: 35% to 68% in hips with osteoarthritis requiring THA [6,14] and 8% in anatomic specimens [7]. The only study investigating prevalence in hips with cam-type FAI without advanced osteoarthritis reported a prevalence of 44%, which is higher than in our cohort [15].…”
Section: ) (B)contrasting
confidence: 51%
See 1 more Smart Citation
“…There are several studies available describing the prevalence of a slip-like morphology for different study populations. A prevalence of 13% was found for healthy young adults [9]: 35% to 68% in hips with osteoarthritis requiring THA [6,14] and 8% in anatomic specimens [7]. The only study investigating prevalence in hips with cam-type FAI without advanced osteoarthritis reported a prevalence of 44%, which is higher than in our cohort [15].…”
Section: ) (B)contrasting
confidence: 51%
“…Such a slip-like morphology has already been described in previous studies based on an osteologic collection [7] or conventional radiographs [13,15]. Drawbacks of these studies included lack of clinical information [7], a potential influence of secondary degenerative changes [14], and/or the use of two-dimensional (2-D) plain radiography [13,14] to evaluate a threedimensional (3-D) problem.…”
Section: Introductionmentioning
confidence: 79%
“…18 Although this problem is said to be rare in children, it appears to be a common cause of hip OA in adults. 18,38 It is the most common aetiology for hip OA in persons < 60 years of age (35.7%) 39 and for nearly half of cam-type FAI cases (43.7%) in our study. This supports our view that a portion of SUFE cases are not being detected.…”
Section: Discussionmentioning
confidence: 49%
“…However, some authors believe it useful and even superior to other radiographic incidences for FAI [12,16]. Several studies have demonstrated the values of interest [2,4,5,[17][18][19]. One of its advantages is that there is no accurate coding for the classic FL.…”
Section: Discussionmentioning
confidence: 99%